PENGARUH COMPANY SIZE DAN LEVERAGE TERHADAP TAX MANAGEMENT - Rianto Rianto; Dede Mutiara Nuraisyah (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to examine the effect of firm size and leverage on tax management. In this study, tax management is measured using the effective tax rate (ETR), company size is measured using SIZE and leverage is measured using the debt ratio (Debt Ratio). The sample used in this study were mining companies listed on the Indonesia Stock Exchange and publishing their annual financial reports in 2016-2020 with 30 companies selected using the purposive sampling method, obtained 60 data from 12 companies with five years of observation. The results of this study indicate that firm size has no significant effect on tax management while leverage has a significant effect on tax management.